تحليل وصفي لأنماط التفاعل في فصول اللغة الإنجليزية كلغة أجنبية في الجامعات الليبية - الشبوكي MUWAHIB MOHAMMED ABDULSALAM (مجلة الاصالة, 2026)
Classroom interaction plays a central role in shaping opportunities for language learning, particularly in English as a Foreign Language (EFL) contexts where exposure to authentic language use is limited. This descriptive study investigates classroom interaction patterns in Libyan university EFL classes, with a specific focus on how teachers and students engage in spoken discourse during regular instructional sessions. The study aims to describe the dominant types of interaction, the distribution of talk, and the extent to which interaction is teacher-centered or learner-oriented. Data are collected through non-participant classroom observations and audio-recorded lessons across selected Libyan universities. The analysis focuses on recurrent interactional sequences, such as teacher questions, student responses, feedback moves, and peer interaction. The findings are expected to reveal a predominance of traditional interaction patterns, characterized by teacher control of discourse, while also highlighting emerging practices that allow greater student participation. By providing a detailed description of actual classroom interaction, this study contributes empirical evidence to the under-researched Libyan EFL context and offers pedagogical insights for enhancing communicative opportunities in university classrooms.